Blaschkitis del adulto como fenómeno paraneoplásico. A propósito de un caso - Arratia S., Isabel; Aguilera S., Camila; Zamorano D., Sofía; Corradini K., Eduardo; Delgado B., Magdalena (Revista Hospital Clínico Universidad de Chile, 2024)
Blaschkitis is an inflammatory skin eruption that that can manifest following the lines of Blaschko. Clinically, it manifests as a recurrent papulovesicular inflammatory dermatitis with a linear distribution. The lesions may appear as narrow lines, though more frequently as broad bands, affecting the trunk either unilaterally or bilaterally. This condition is typically observed in middle-aged individuals. We present the case of an 81-year-old male with a one-year history of an inflammatory plaque in the abdominal region. Histopathological examination of the lesion revealed features consistent with a paraneoplastic syndrome.